Frequency of Anxiety and Depression in Patients of Epilepsy - Omer Jalal, Usman Ahmad, Muhammad Siddique Kakar, Anza Muhammad, Minal Fatima, Sadaf Hammad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Millions of people have epilepsy, which is a chronic condition that significantly increases mortality as well as morbidity. For numerous causes, anxiety in epilepsy is currently gaining attention. The objective of this study is to determine the frequency of anxiety and depression in patients suffering from epilepsy Study design and Setting:This was a cross sectional study. This study was conducted at Departments of Neurology and Psychiatry, Combined Military Hospital (CMH), Multan from March, 2023 to August 2023 Methodology:Total 200 patients newly diagnosed patients of epilepsy with less than or equal to 06 months history of the disease. HADS (Urdu version) was used for assessment. HADS consists of 14 questions followed by four options that are on a continuum of severity/intensity of symptoms. Statistical Package for Social Sciences version 20 was used for the calculations Results:The finding showed that the mean age of all 200 patients was 31.20±6.97 years, 123(61.5%) male and 77(38.5%) female patients in the study. Based on the analysis, the hospital anxiety and depression scale there were 62(31%) patients who had depression and 47(23.5%) patients had anxiety Conclusion:The study concluded that, epilepsy sufferers had rather high levels of anxiety and depression. Health care professionals should pay close attention to screening, early detection, and proper therapy of depression and anxiety in persons with epilepsy. Keywords: Epilepsy, Anxiety, Depression